2014
DOI: 10.1155/2014/594354
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of the Components from Shengmai Injection towards UDP‐Glucuronosyltransferase

Abstract: The mechanism of shengmai injection- (SMI-) related drug-drug interaction remains unclear. Evaluation of the inhibition potential of SMI's ingredients towards UDP-glucuronosyltransferases (UGTs) activity will provide a new insight to understand SMI-related drug-drug interaction. In vitro incubation system to model UGT reaction was used. Recombinant UGT isoforms-catalyzed 4-methylumbelliferone (4-MU) glucuronidation and UGT1A4-catalyzed trifluoperazine (TFP) glucuronidation reactions were employed to phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Three-week SMS treatment decreased the maximal velocity of intestinal nifedipine oxidation by 50%, while the CYP3A protein level remained unchanged; among the SMS component herbs, the decoction of Ophiopogonis Radix decreased the intestinal nifedipine oxidation activity [195]. Based on an inhibition kinetic investigation of various UGT isoforms, ophiopogonin D was found to noncompetitively inhibit UGT1A6 (K i , 20.6 µmol/L) and competitively inhibit UGT1A8 (40.1 µmol/L); ophiopogonin D' noncompetitively inhibited UGT1A6 (5.3 µmol/L) and UGT1A10 (9.0 µmol/L); and ruscorectal competitively inhibited UGT1A4 (0.02 µmol/L) [106]. The ginsenoside Rg 1 , ophiopogon D', and schisandrin A are potential inhibitors of sodium taurocholate co-transporting polypeptide (NTCP) and probably interact with NTCP-modulating clinical drugs.…”
Section: Shengmai Formulamentioning
confidence: 99%
“…Three-week SMS treatment decreased the maximal velocity of intestinal nifedipine oxidation by 50%, while the CYP3A protein level remained unchanged; among the SMS component herbs, the decoction of Ophiopogonis Radix decreased the intestinal nifedipine oxidation activity [195]. Based on an inhibition kinetic investigation of various UGT isoforms, ophiopogonin D was found to noncompetitively inhibit UGT1A6 (K i , 20.6 µmol/L) and competitively inhibit UGT1A8 (40.1 µmol/L); ophiopogonin D' noncompetitively inhibited UGT1A6 (5.3 µmol/L) and UGT1A10 (9.0 µmol/L); and ruscorectal competitively inhibited UGT1A4 (0.02 µmol/L) [106]. The ginsenoside Rg 1 , ophiopogon D', and schisandrin A are potential inhibitors of sodium taurocholate co-transporting polypeptide (NTCP) and probably interact with NTCP-modulating clinical drugs.…”
Section: Shengmai Formulamentioning
confidence: 99%
“…27), and ophiopogonin D noncompetitively inhibited UGT1A6 while competitively inhibiting UGT1A8. 28 Thus, furocoumarins, ophiopogonins and ophiopogonones presumably might be responsible for the herb-herb pharmacokinetic interaction between GR and OR in rats.…”
Section: Pharmacokinetics Studymentioning
confidence: 99%
“…23 Previous studies have found that MOA inhibits propofol-O-glucuronidation, while its structural analogue ophiopogonin D inhibits both UGT1A6 and UGT1A8. 24,25 These findings suggest that MOA may interact with a panel of hUGTs, but the inhibitory effects of MOA against hUGTs and related molecular mechanism have not been well investigated.…”
mentioning
confidence: 99%